Aortic stiffness in adolescent Turner and Marfan syndrome patients. (19th April 2018) - Schäfer, Michal; Browne, Lorna P; Truong, Uyen; Jaggers, James J; Mitchell, Max B; Malone, Ladonna; Morgan, Gareth; Chatfield, Kathryn; McLennan, Daniel; Turbendian, Harma; Vargas, Danial; Fonseca, Brian; et al.
Abstract: OBJECTIVES: Turner syndrome (TS) and Marfan syndrome (MFS) are partially characterized by aortopathies with a risk of developing severe aortic dilation, stiffness and consequent dissection and aneurysm formation. The incidence of a bicuspid aortic valve (BAV) is also increased in TS. We investigated aortic stiffness in teenage TS and MFS patients and evaluated to what degree stiffness in TS patients is augmented by the presence of a BAV. METHODS: Fifty-seven patients with TS ( n  = 37) and MFS ( n  = 20), as well as 22 controls with similar age and size distribution underwent evaluation of thoracic aortic stiffness using phase-contrast magnetic resonance imaging. Calculated stiffness indices including pulse wave velocity (PWV), distensibility and relative area change (RAC) were collected to characterize the ascending aorta and descending aorta. PWV was also determined to evaluate global aortic arch stiffness. RESULTS: Patients with TS had reduced distensibility (0.43 vs 0.58%/mmHg, P  < 0.05) and RAC (21 vs 29%, P  < 0.01) in the ascending aorta when compared with normal controls. Similarly, patients with MFS had reduced ascending aortic distensibility (0.39 vs 0.58%/mmHg, P  < 0.05) and RAC (22 vs 29%, P  < 0.05). There were no differences in measured PWV in the ascending aorta. Patients with TS had significantly elevated PWV measured in the aortic arch when compared with controls (2.7 vs 1.9 m/s, P  < 0.05). Patients with MFS had more prominent elevation in aortic arch PWV (4.2 vs 1.9 m/s, P  < 0.01). The descending aortas had decreased distensibility (0.36 vs 0.55%/mmHg, P  < 0.05) and RAC (18 vs 25%, P  < 0.01) only in MFS patients. Additionally, 18 TS patients with a BAV were compared with 19 TS patients with a trileaflet aortic valve, without significant differences observed in any of the considered stiffness indices. CONCLUSIONS: TS and MFS teenage patients display evidence of increased aortic stiffness. In TS patients, this is focused in the ascending aorta and is independent of the presence of a BAV. MFS patients display a generalized reduction in compliance of the entire aorta.